Phonetic and Lexical Phenomena of Armenian Dialects Related to Grabar - Mesropyan, Haykanush (Bulletin of Yerevan University B: Philology, 2024)
The article presents the origins of the linguistic richness of the Armenian dialects, phonetic, lexical and grammatical connections with the ancient Armenian Grabar language. The ancient literary Armenian language played a significant role in the formation and development of Central Armenian and new literary languages, replenishing the dialect vocabulary. Several key questions are posed and addressed: 1) различные фонетические проявления с древнеармянской-грабарской основой, 2) cases of preserving the root form of a word, 3) features of phonetic and lexical parallelisms, 4) words and phrases that are not included in the vocabulary of the literary language, but are preserved in dialects, 5) features of the use of native Armenian root words, etc. Through research, we found out that in the course of historical development, the dialects of the Armenian language were supplemented and enriched with various phonetic, lexical and grammatical means based on grabar. Words that are not included in the dictionary of a literary language, but preserved in dialects, with old and new meanings, help to identify some linguistic issues, as well as make etymological corrections.